2008
DOI: 10.1002/jmv.21093
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and functional analysis of five HPVE6 variants with respect to p53 degradation

Abstract: Persistent infection with high risk human papillomavirus is a necessary risk factor in the etiology of invasive cervical carcinoma. With regard to molecular details, the best studied types are HPV16 and HPV18 which are found in 70% of cervical cancer worldwide, however factors associated with the progression of individual cervical intraepithelial neoplasias into cancer are still poorly understood. Intratype amino acid variations in the immortalizing and transforming early proteins E6 and E7 were described to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…p53 is a well-known tumor suppressor gene, and an increase in p53 levels plays a critical role in the induction of genes that results in cell cycle arrest [ 7 ], allowing repair of damaged DNA or activation of apoptotic pathways [ 8 ]. In cervical cancer with high risk of HPV-infection, the E6 protein from high-risk HPV can bind to tumor suppressor protein p53 for rapid degradation via a cellular ubiquitin ligase [ 9 ]. Other studies have indicated that p53 protein over-expression is not common or associated with survival in cervical carcinoma [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…p53 is a well-known tumor suppressor gene, and an increase in p53 levels plays a critical role in the induction of genes that results in cell cycle arrest [ 7 ], allowing repair of damaged DNA or activation of apoptotic pathways [ 8 ]. In cervical cancer with high risk of HPV-infection, the E6 protein from high-risk HPV can bind to tumor suppressor protein p53 for rapid degradation via a cellular ubiquitin ligase [ 9 ]. Other studies have indicated that p53 protein over-expression is not common or associated with survival in cervical carcinoma [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Figure 7 shows a summary of recent data on how the E6 proteins of different types affect the steady-state levels of p53 and Magi1c and hDLG (PDZ-containing proteins; Hiller et al , 2006; Hiller et al , 2008; Muench et al , 2009). This tree, based on the nucleotide sequence of the E6 proteins, clusters all the oncogenic types (Bouvard et al , 2010) in a single (red) HR-clade; however, not all members of this clade actually cause disease.…”
Section: Toward a Biochemical Understanding Of Alphapapillomavimentioning
confidence: 99%
“…column shows the epidemiological classification (oncogenic, OT; nonOT, NOT, insufficient data, N/A) according to Bouvard et al (2010). The following columns summarize the data presented in p53 (1) (Hiller et al , 2006), p53 (2) (Hiller et al , 2008), p53 (3) (Fu et al , manuscript submitted), Magi1c (4), and hDLG (4) (Muench et al , 2009). In these columns, “yes” indicates degradation of the target, “no” means no degrading potential, and “~” signifies intermediate potential.…”
Section: Figurementioning
confidence: 99%
“…In addition, Hiller et al . [29] recently stated that several variants of HPV E6 protein may play a role in supporting increased viral persistence by avoiding immune responses.…”
Section: Current Understanding Of Sccamentioning
confidence: 99%
“…It is therefore likely that E6‐mediated abrogation of p53 protein‐dependent apoptosis has the equivalent effect to inactivating mutations of the p53 gene [26]. In addition, Hiller et al [29] recently stated that several variants of HPV E6 protein may play a role in supporting increased viral persistence by avoiding immune responses.…”
Section: Current Understanding Of Sccamentioning
confidence: 99%